Factors Influencing Behavioral Intention of Online Learning in the Post-Covid Pandemic: A Case Study of a Primary School in Chengdu, China - Guanfu, Chen (Scholar: Human Sciences, 2023)
Purpose: This research aims to determine influencing factors of primary school students’ behavioral intention to use online learning in the post-epidemic in Chengdu, China. The conceptual framework contains perceived ease of use, perceived usefulness, attitude, habit, social influence, perceived behavioral control and behavioral intention. Research design, data, and methodology: Population and sample size are 450 parents of students who have been experiencing online learning at least one semester in one of a top primary school in Chengdu, China. The sample techniques used were judgmental, quota, and convenience samplings. Before the data collection, the results of index of item objective congruence (IOC) and Cronbach’s Alpha coefficient values were approved. Afterward, confirmatory factor analysis (CFA) and structural equation modeling (SEM) were applied to measure validity, reliability, goodness of fit and hypotheses testing. Results: Perceived ease of use significantly influences perceived usefulness and attitude. Perceived usefulness has a significant influence on attitude. Attitude and perceived behavioral control significantly influence behavioral intention. Nevertheless, habit and social influence had no significant influence on behavioral intention of online learning among primary school students. Conclusions: Students were isolated and banned from physical classroom due to the spread of the virus, therefore, the Chinese government carried on the education as well as use online education to solve the imbalance for Chinese students via online learning during to post-epidemic.